A rare presentation: Brain abscess secondary to urinary tract infection - Teresa Frazão, MD; Ana Patrícia Brito, MD; Joana Cerdeira Frazão, MD; Elisabete Ribeiro, MD; Jorge Cotter, MD (Radiology Case Reports)
Cerebral abscess due to hematogenous spread originating from a urinary infection is a rare condition. This clinical case involves an 80-year-old woman with a history of recurrent urinary infections. She presented to the emergency department with fever and altered consciousness. Complementary diagnostic studies were performed, and unexpectedly, a CT scan revealed an intraparenchymal abscess. It is noteworthy that this clinical case is rare due to its initial presentation, as there are many other causes that could explain it.